Strategic solutions for corporate restructuring - Bivainis, Juozas; Tamošiūnas, Andrius (International Journal of Strategic Property Management, 2004)
The paper analyses solutions of corporate restructuring, specifying the techniques of their application in the context of improvement of strategic management, rationalization of corporate management functions as well as measures to control the restructuring process. The benefit of application of the proposed corporate restructuring solutions is revealed. Greater possibilities to rationalize the restructuring process, use of human potential, material and financial assets, other relevant strategic corporate property, to develop resources of an enterprise and thus to reach greater competitiveness of enterprises are created. First Published online: 18 Oct 2010